Heterogeneity of Stomatal Pore Area Is Suppressed by Ambient Aerosol in the Homobaric Species, Vicia faba - Grantz, David A.; Karr, Marcus; Burkhardt, Juergen (Frontiers in Plant Science, 2020)
Stomatal pore area is heterogeneous across leaf surfaces. This has been considered as “patchy stomatal conductance”, and has substantial implications for photosynthetic efficiency. Aerosols have always been important elements of plant environments, but their effects on stomatal control of plant water relations, and stomatal heterogeneity specifically, has not been widely considered. Here we evaluate the spatial coordination of between pore area in the glabrous and homobaric leaves of Vicia faba. We construct a large dataset (n > 88,000 discrete comparisons) of paired pore areas and distances between the pores. Plants were grown in ambient urban air and in filtered air to determine the effect of ambient aerosol on stomatal properties. Pore area exhibited spatial organization, as well as considerable variability among closely co-located pores. Difference in pore area were positively correlated with distance between the pores in both treatments. However, aerosol deposition reduced both the magnitude of variability between pores and the rate at which this variability increased with pore separation distance. These data support previous conclusions that deposition of hygroscopic aerosol may create a thin aqueous film across the leaf surface that connects neighboring stomata to each other and to the leaf interior. Aerosol impacts on stomatal heterogeneity and gas exchange are not adequately considered in current assessments of stomatal control.